2022
DOI: 10.1155/2022/1310030
|View full text |Cite
|
Sign up to set email alerts
|

Excess Weight and Body Fat Percentage Associated with Waist Circumference as a Cardiometabolic Risk Factor in University Students

Abstract: Background. Obesity is one of the most important public health problems for university students. The objective of the study was to evaluate the association between body mass index (BMI) and body fat percentage (%BF) with waist circumference (WC) as a cardiometabolic risk factor (CMR) among university students. Methods. A cross-sectional study was carried out in 2,048 students from a private university located in Lima, Peru. Anthropometric data (weight, height, %BF, and WC) were collected. Chi-square test was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…[39][40][41] In fact, the university is one of the most important settings that affect the eating habits and physical and mental well-being of faculty, staff, and students. 42,43 In addition, it is reported that teachers perform academic work in their free time, 35 this could lead to high levels of work-related stress, which in turn negatively impacts eating habits and physical activity. 44 Therefore, the use of motivation as part of the components of telehealth-based interventions is crucial for improving lifestyles to achieve a significant decrease in the risk of non-communicable diseases and avoid absenteeism of university faculty and staff due to medical conditions related to unhealthy behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] In fact, the university is one of the most important settings that affect the eating habits and physical and mental well-being of faculty, staff, and students. 42,43 In addition, it is reported that teachers perform academic work in their free time, 35 this could lead to high levels of work-related stress, which in turn negatively impacts eating habits and physical activity. 44 Therefore, the use of motivation as part of the components of telehealth-based interventions is crucial for improving lifestyles to achieve a significant decrease in the risk of non-communicable diseases and avoid absenteeism of university faculty and staff due to medical conditions related to unhealthy behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…3941 In fact, the university is one of the most important settings that affect the eating habits and physical and mental well-being of faculty, staff, and students. 42, 43 In addition, it is reported that teachers perform academic work in their free time, 35 this could lead to high levels of work-related stress, which in turn negatively impacts eating habits and physical activity. 44…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in university students found that 61.1% of male university students had excess body fat measured by BIA (InBody), recommending to implement healthy lifestyle initiatives, particularly among male students and those who are overweight or obese (Nuñez-Leyva et al 2022). On the contrary, we found that body fat percentage among Saudi male university students in the current study is considerably normal (mean± SD= 15.62 ± 5.54%) and within healthy ranges that fell below the level of 25% for males according to the American Council on Exercise (Gallagher et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of obesity is multifactorial. The most important related causes are physiological factors characterized by changes in the amount and distribution of body fat; 5 environmental factors, such as lack of physical activity, 6 unhealthy eating habits, 7 and lack of adequate nutritional knowledge about healthy eating. 8 , 9 Excess body weight considerably increases the risk of morbidity and mortality from chronic diseases such as diabetes mellitus, cardiovascular disease, and hypertension.…”
Section: Introductionmentioning
confidence: 99%